Smart nanoplatforms for early detection and immune modulation in lung cancer - Yu, Chaoxiao; Xia, Haiying; Wang, Yanqing; Liu, Xueping (Frontiers in Bioengineering and Biotechnology, 2026)
Lung cancer is a major cause of cancer related mortality due to delayed diagnosis and limited therapeutic efficiency. Early detection and effective immune modulation are important to control lung cancer. Advancements in nanotechnology have improved oncology due to sensitive, specific, and minimally invasive detection platforms along with immune regulatory therapeutic approaches. Smart nanoplatforms fabricated with high precision and responsiveness have the ability to treat diseases as well as the immune system. These systems combine functional nanomaterials with biomolecular recognition elements to detect biomarkers such as exosomes, DNA, RNA, and proteins. They also facilitate targeted immune activation through checkpoint inhibition, nanovaccines, and tumor microenvironment reprogramming. Moreover, artificial intelligence and machine learning are enhancing the interpretation of complex data, which increases the diagnostic accuracy and predictive power. Despite advances in diagnostic and immune modulation, there are also several challenges related to biological barriers and biocompatibility. This review comprehensively explains the molecular basis of lung cancer, recent progress in nanotechnology based diagnostics and immunotherapy, and the design of multifunctional smart nanoplatforms. Future studies emphasize integrating personalized medicine, digital modeling, and bioinspired nanosystems for clinically translatable solutions in early lung cancer management.